Assigning distinct identities to sites on an anonymous distributed system - Helary, J.-M.; Raynal, M. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A distributed algorithm that assigns distinct and ordered identities to the sites of a connect anonymous distributed system is presented. The basis for this algorithm is the sequential distributed traversal scheme, the sequential aspect of which ensures that all sites are systematically visited in mutual exclusion. Such an algorithm allows the definition of sites to be independent of particular of initial values (as far as identities are concerned).< >